Treatment adherence to disease-modifying antirheumatic drugs in Chinese patients with rheumatoid arthritis - Xia Y; Yin R; Fu T; Zhang L; Zhang Q; Guo G; Li L; Gu Z (Patient Preference and Adherence, 2016)
Yunfei Xia,1,* Rulan Yin,1,2,* Ting Fu,1,2 Lijuan Zhang,1,2 Qiuxiang Zhang,1,2 Genkai Guo,1 Liren Li,2 Zhifeng Gu11Department of Rheumatology, Affiliated Hospital of Nantong University, 2School of Nursing, Nantong University, Nantong, People’s Republic of China *These authors contributed equally to this work Objective: Nonadherence in rheumatoid arthritis (RA) patients using disease-modifying antirheumatic drugs (DMARDs) may lead to joint damage and function loss. The aim of this cross-sectional study was to explore Chinese RA patients’ adherence rates and investigate potential risk factors for nonadherence.Methods: A total of 122 RA patients were recruited from the Affiliated Hospital of Nantong University from January 2014 to April 2015. Patients were asked to complete a set of standardized self-report questionnaires (Compliance Questionnaire on Rheumatology, Health Assessment Questionnaire, Short Form-36 questionnaire, 28-joint Disease Activity Score, Hospital Anxiety and Depression Scale, and Visual Analog Scale). Independent samples t-tests, chi-square analyses, and logistic regression modeling were used to analyze these data.Results: Based on Compliance Questionnaire on Rheumatology, 38% of the patients adhered to DMARDs. Adherence was associated with education, income, depression, and the total number of DMARDs. Other demographic and clinical characteristics were not associated with adherence. Logistic regression models identified income, depression, and the total number of DMARDs as predictors of medication nonadherence.Conclusion: In this study, 62% of patients with RA were not adherent to their DMARD prescription. Education, income, depression, and the total number of DMARDs were associated with medication adherence, and income, depression, and the total number of DMARDs were independent predictors of medication adherence in patients with RA. These findings could help medical personnel develop helpful interventions to improve adherence in RA patients by paying more attention to the patients with these accompanying risk factors and, finally, improve RA patients’ quality of life.Keywords: rheumatoid arthritis, disease-modifying antirheumatic drugs, adherence